Considerations agenesis of the vagina. Study of 4 cases - Salazar, Wenceslao (2015)
We have studied four cases of agenesis of Vagina, aged between 15 and 20 years; all had normal size and adequate breast development; in 3 of them sexual chromatin was 32, 18 and 12% and the determination of 17-ketosteroids was normal, the pregnanediol was found in figures proliferative phase, although in one case basal temperature curve indicating ovulation was seen; on x-ray images that appeared to correspond to gonads they showed. The treatment of the four patients was the creation of the neo-vagina simple reconstruction method with good results.